A Creative Intervention: Mandala Art Therapy and Midwifery in Women's Health - Rabia Ekti Genç, Etki Genç, Genç Ekti, Ekti; Buket Akkurt (Ebelik ve Sağlık Bilimleri Dergisi, 2025)
Art therapy covers all mind-body based approaches applied as a method to improve the psychological health of the individual in the presence of illness or any difficulty experienced by the individual. Art therapies allow the abstract and complex thoughts in the individual's mind to become concrete. One of the many different types of art therapy involves mandala. Mandala, which has a deep-rooted history, is used in art therapy today. The ease of use and accessibility of mandalas for people of all age groups have contributed positively to the treatment of various diseases. From this perspective, mandala art therapy may be beneficial for different periodic life crises in women's lives. Midwives are health professionals who play a key role in every stage of women's health. Innovative midwifery approaches to create positive results in care at all stages of women's health are also nourished by spiritual and artistic practices. The International Confederation of Midwives has also developed a holistic and continuous care model in its midwifery care philosophy, covering women's social, emotional, spiritual, cultural, psychological and physical experiences. In line with this model, midwives' incorporating spiritual and artistic therapy methods in their care practices at all stages of women's health can make a difference in the quality of care. In this review, it is aimed to investigate the application areas of mandala art therapy in the field of midwifery, to evaluate the results of mandala art therapy in these areas and to identify gaps in the literature.